Consistent copy number changes and recurrent PRKAR1A mutations distinguish Melanotic Schwannomas from Melanomas: SNP‐array and next generation sequencing analysis. Issue 8 (29th May 2015) - Wang, Lu; Zehir, Ahmet; Sadowska, Justyna; Zhou, Nengyi; Rosenblum, Marc; Busam, Klaus; Agaram, Narasimhan; Travis, William; Arcila, Maria; Dogan, Snjezana; Berger, Michael F.; Cheng, Donavan T.; et al.
<x xml:space="preserve">Abstract</x> Melanotic Schwannomas (MS) are rare tumors that share histological features with melanocytic tumors and schwannomas. However, their genetics are poorly understood. To elucidate the genetic characteristics of MS, we performed genome‐wide studies in a series of cases. Twelve MS cases were available for the study. Genomic DNAs extracted from formalin‐fixed paraffin embedded tumor tissues were subjected to copy number (CN) and allelic imbalance (AI) analysis by Single Nucleotide Polymorphism (SNP)‐array and screened for mutations in coding exons of 341 key cancer‐associated genes using a hybrid capture‐based next‐generation sequencing (NGS) assay. Sanger sequencing was used to further verify recurrent mutations detected by NGS study. SNP‐array analysis revealed remarkably stereotypic chromosomal abnormalities in MS. Hypodiploidy was common, typically involving monosomies of chromosomes 1, 2, and 17. All 12 samples showed mutations in PRKAR1A gene, including 2 cases with 2 mutations each. The 14 mutations were scattered across PRKAR1A, and most were inactivating mutations. AI on 17q, presenting as loss of heterozygosity with or without CN losses, combined with a PRKAR1A mutation was observed in 9/12 MS cases. The remaining 3 cases included the two samples harboring two mutations in PRKAR1A. MS exhibits a stereotypic pattern of chromosomal losses. In contrast, melanomas are typically characterized by the presence of multiple CN aberrations, without demonstrable differences in the frequency of losses and gains. Inactivation of both alleles of PRKAR1A by "two hits" observed in almost all cases underscores the central role of PRKAR1A in the pathogenesis of this neoplasm. © 2015 Wiley Periodicals, Inc.